Deformation history of the Puna plateau, Central Andes of northwestern Argentina. (November 2020) - Henríquez, Susana; DeCelles, Peter G.; Carrapa, Bárbara; Hughes, Amanda N.; Davis, George H.; Alvarado, Patricia
Abstract: Two tectonic shortening events created the first-order structural characteristics of the Puna plateau: one in the Paleozoic and a second during the Andean Orogeny in the Cenozoic. To constrain the structural characteristics and timing of Andean deformation in the Puna plateau, we focus on differentiating these two shortening events and provide cooling ages (apatite fission track and apatite (U–Th)/He) to determine the amount of Andean exhumation on the hanging-wall of major Cenozoic faults. Two contrasting expressions of shortening are documented. In Ordovician strata, strain requires four stages: folding, flattening through cleavage formation, low-angle faulting and local distributed shear. In the Mesozoic and Cenozoic strata, shortening is expressed as reverse faults, fault-propagation folds and dipping panels. Dissimilarities reflect different P-T conditions and amount of strain, as structures in the Ordovician rocks require higher temperatures and strain than Andean structures in the Mesozoic and Cenozoic strata. Furthermore, local Cretaceous AFT cooling ages in pervasively cleaved Ordovician rocks reveal these rocks did not reach temperatures compatible with cleavage formation during the Andean event. Lastly, our data show a middle Eocene to Oligocene exhumation history that supports an overall continuous development of the Andean thrust belt in the Puna plateau since the early Cenozoic. Highlights: Apatite fission track and apatite (U–Th)/He ages show middle Eocene to Oligocene exhumation. Exhumation history evidence the eastward propagation of the thrust belt in the Puna plateau. Strain in the Ordovician strata requires Paleozoic folding, flattening and pressure dissolution. Cretaceous AFT ages in the western Puna evidence limited Cenozoic exhumation and erosion. The thrust belt experienced internal deformation during Oligocene and Miocene times.